Role of 17β-Estradiol on Cell Proliferation and Mitochondrial Fitness in Glioblastoma Cells. (14th February 2020) - Castracani, Carlo Castruccio; Longhitano, Lucia; Distefano, Alfio; Anfuso, Daniela; Kalampoka, Stavroula; La Spina, Enrico; Astuto, Marinella; Avola, Roberto; Caruso, Massimo; Nicolosi, Daria; Giallongo, Cesarina; Tibullo, Daniele; et al.
Abstract : Gliomas are the most common primary tumors of the central nervous system (CNS) in the adult. Previous data showed that estrogen affects cancer cells, but its effect is cell-type-dependent and controversial. The present study aimed to analyze the effects of estradiol (E2, 5 nM) in human glioblastoma multiforme U87-MG cells and how it may impact on cell proliferation and mitochondrial fitness. We monitored cell proliferation by xCELLigence technology and mitochondrial fitness by assessing the expression of genes involved in mitochondrial biogenesis (PGC1α, SIRT1, and TFAM), oxidative phosphorylation (ND4, Cytb, COX-II, COX IV, NDUFA6, and ATP synthase), and dynamics (OPA1, MNF2, MNF1, and FIS1). Finally, we evaluated Nrf2 nuclear translocation by immunocytochemical analysis. Our results showed that E2 resulted in a significant increase in cell proliferation, with a significant increase in the expression of genes involved in various mechanisms of mitochondrial fitness. Finally, E2 treatment resulted in a significant increase of Nrf2 nuclear translocation with a significant increase in the expression of one of its target genes (i.e., heme oxygenase-1). Our results suggest that E2 promotes proliferation in glioblastoma cells and regulate the expression of genes involved in mitochondrial fitness and chemoresistance pathway.